Development and Characterization of Cefoxitin Loaded D,L-PLA Nanoparticles - S.R.P. Machado; R.C. Evangelista (São Paulo State University (UNESP), 2010)
Nanoparticles containing cefoxitin (CEF) made of D,L-PLA (PLA) were designed by a multiple emulsion/solvent evaporation method. The particles were extensively evaluated in relation to morphology, encapsulation efficiency, drug-polymer interactions as well as in vitro drug release kinetics. Nanoparticles were spherical in shape and isolated, with a mean diameter of about 600 nm. The thermal behaviour (DSC) of CEF-containing nanoparticles suggested that the drug was dispersed at a molecular level within the system. The drug encapsulation efficiency in the system for a CEF concentration of 30 mg/mL was 5.5%, as assessed after the drug extraction, by a validated HPLC method. This low encapsulation efficiency is understandable, since CEF is highly hydrophilic. The in vitro assays showed a strong sustained drug release profile from the nanoparticles with kinetics following pure Fickian diffusion.